Global urban reforestation can be an important natural climate solution. (3rd March 2021) - Teo, Hoong Chen; Zeng, Yiwen; Sarira, Tasya Vadya; Fung, Tze Kwan; Zheng, Qiming; Song, Xiao Ping; Chong, Kwek Yan; Koh, Lian Pin
Abstract: The climate mitigation potential of urban nature-based solutions (NBSs) is often perceived as insignificant and thus overlooked, as cities primarily pursue NBSs for local ecosystem services. Given the rising interest and capacities in cities for such projects, the potential of urban forests for climate mitigation needs to be better understood. We modelled the global potential and limits of urban reforestation worldwide, and find that 10.9 ± 2.8 Mha of land (17.6% of all city areas) are suitable for reforestation, which would offset 82.4 ± 25.7 MtCO2 e yr −1 of carbon emissions. Among the cities analysed, 1189 are potentially able to offset >25% of their city carbon emissions through reforestation. Urban natural climate solutions should find a place on global and local agendas.